The Promise of Collective Action for Large-Scale Commons Dilemmas: Reflections on Common-Pool-Resource Theory. Issue 1 (27th April 2022) - Yoder, Landon; Wagner, Courtney Hammond; Sullivan-Wiley, Kira; Smith, Gemma
It has become axiomatic that collective action is core to overcoming commons dilemmas. However, the popularity of the commons dilemma framing has led to its decoupling from canonical common-pool-resource cases. This decoupling is especially problematic for theorizing under what conditions collective action would emerge to solve complex, large-scale environmental problems, such as climate change, biodiversity loss, or ocean hypoxia. We argue that there is an over-emphasis on using diagnostic tools (e.g., the design principles), which has come at the expense of theory building for non-canonical cases. Canonical cases, such as fisheries, forests, or irrigation networks, rely on situations where salience of social dilemmas arises from joint costs and benefits actors face from allocating and sustaining a shared pool of livelihood-dependent resources. By expanding the commons definition to more generally mean shared needs or benefits, such as ecosystem services, the consequences of uses in large-scale CPRs, such as pollution, become less obvious. In this paper, we argue that it is particularly urgent to generate a revised theory of collective action for these types of cases, where environmental bads are core to the social dilemma. We contend that Ostrom's design principles represent a particular set of solutions to several interconnected and foundational aspects of group problem-solving: generating salience, achieving widespread participation, and ensuring compliance over time. We argue that reconceptualizing how particular institutional arrangements address salience, participation, and compliance can expand CPR theory's applicability to these large-scale problems and help to clarify the role that collective action can play in solving these pressing challenges.